The Relationship of Parents' Economic Level with Junior High School Students' Interest in Choosing Culinary Skills Competencies at Vocational School - Avrilla Saldi Putri; Elida Elida; Asmar Yulastri; Wiwik Gusnita (Educia Journal, 2026)
This research is motivated by the importance of student interest in determining the choice of skill competencies in Vocational High Schools (SMK), which is thought to be influenced by the economic level of parents. This research aims to describe the economic level of parents, describe the interests of junior high school students in choosing Culinary Skills Competencies at SMK Negeri 1 Painan, and analyze the relationship between the economic level of parents and the students' interests. This research uses a quantitative approach with a correlational type of research. The research population was 663 class IX students of State Middle Schools in IV Jurai District, with a sample of 87 respondents determined using the Slovin formula and proportional random sampling technique. Data was collected via questionnaire and analyzed using descriptive statistics and Pearson Product Moment correlation. The research results show that the parents' economic level is in the medium category with an average score of 31.32, while students' interest in choosing Culinary Skills Competencies is in the high category. The results of the correlation test show a value of r = 0.678 with a significance of 0.000 < 0.05, which means there is a strong and significant positive relationship between the economic level of parents and students' interest in choosing Culinary Skills Competencies at SMK Negeri 1 Painan. The coefficient of determination (R²) value of 0.460 indicates that 46.0% of the variation in student interest can be explained by the economic level of parents. Thus, the higher the parents' economic level, the higher the student's interest in choosing the Culinary Skills Competency at SMK Negeri 1 Painan.